Global change induced biomass growth offsets carbon released via increased forest fire and respiration of the central Canadian boreal forest. Issue 5 (30th May 2017) - Gonsamo, Alemu; Chen, Jing M.; Colombo, Stephen J.; Ter‐Mikaelian, Michael T.; Chen, Jiaxin
Abstract: Northern boreal forests are sensitive to many effects of global change. This is of particular concern due to the proportionally greater climate change projected for the area in which these forests occur. One of the sensitive areas is the Far North of Ontario (FNO), consisting of one of the world's largest remaining tracts of unmanaged boreal forest, the world's third largest area of wetland, and the most southerly area of tundra. We studied past, present, and potential future carbon (C) balance of FNO forests using the Integrated Terrestrial Ecosystem Carbon Model and the Canadian Regional Climate Model with stand‐replacing fire disturbance. The forced simulations of past (1901–2004) C balances indicated that vegetation C stock remained stable, while soil C stock gradually declined (−0.07 t C ha −1  yr −1, p  < 0.001), resulting in an overall significant decrease in total ecosystem C balance (−0.07 t C ha −1  yr −1, p  < 0.001). Two Representative Concentration Pathways (RCPs), RCP8.5 and RCP4.5, simulations of future (2007–2100) C balances indicated that the carbon dioxide fertilization and climate growth‐enhancing effects of global change will outweigh C loss through increased ecosystem respiration, disturbance, and changes in forest age class structure resulting in an increase in total FNO ecosystem C stock by mid‐21st century. However, the projected simulations also indicated that the relative sizes of forest C stocks will change, with relatively less in the soil and more in vegetation, increasing fuel loads and making the entire ecosystem susceptible to forest fire and insect disturbances. Plain Language Summary: Northern boreal forests are sensitive to many effects of changes in climate and forest disturbances. This is of particular concern due to the disproportionally greater climate change projected for the area in which these forests occur. We studied past and potential future carbon balance of the Far North of Ontario (FNO), consisting of one of the world's largest remaining tracts of unmanaged boreal forest, the world's third largest area of wetland, and the most southerly area of tundra. Our results suggest that historically, for the period of 1901–2004, the total carbon stored in 172, 155 km 2 unmanaged forests of FNO decreased in average by 7.28 t carbon per hectare. This decline is linked to the increased soil carbon release and organic matter decomposition in response to the steady increase in mean air temperature. Future simulations for 2007–2100 indicate the biomass increase due to warming and fertilization from the increasing atmospheric CO2 concentration will outweigh carbon loss through increased soil carbon release and fire disturbance. The future simulations also show decreased carbon stored in soil and increased carbon stored in vegetation compared to the historic values. This will increase fuel loads and make the entire ecosystem susceptible to potential fire and insect disturbances. Key Points: Historical and projected C balance of unmanaged Canadian boreal forest Projected biomass increase exceeds soil C loss Global change increases biomass C stock and decreases soil C stock